Kondisi Tingkat Pendidikan Masyarakat di Lingkungan VI Kelurahan Nalu Kecamatan Baolan Kabupaten Tolitoli - Ika Listiqowati; Fitri Handayani (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2020)
This study aims to 1) describe the condition of community education level in Ward VI, Nalu Village, Baolan District, Tolitoli Regency. 2) describe the condition factors of community education level in Ward VI, Nalu Village, Baolan District, Tolitoli Regency. This type of research is descriptive qualitative, the subject of research is the community in Environment VI Nalu Village consisting of local government represented by the chairman of environment VI, and 14 residents of Environment VI as key informants. Data collection method using observation method, interview, and documentation. Data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The results showed that: 1) the condition of community education in Environment VI Nalu Village, Baolan District, Tolitoli Regency is still low, this is evidenced by the number of people who do not get education and there are also people who only take elementary education (SD). 2) Factors that cause low levels of public education in Environment VI are individual motivation factors, economic factors, social factors, and accessibility factors.